Development of polymorphic microsatellite loci in the perennial herb Hepatica nobilis var. japonica (Ranunculaceae)(1) - Kameoka, Shinichiro (Appl Plant Sci, 2015)
PREMISE OF THE STUDY: Microsatellite markers were developed and characterized in the vulnerable plant Hepatica nobilis var. japonica (Ranunculaceae) to investigate its genetic diversity, population structure, and gene flow. METHODS AND RESULTS: Fourteen microsatellite markers were developed. The number of alleles per locus ranged from one to 12, and the expected heterozygosity per locus ranged from 0.043 to 0.855. Eleven markers were successfully amplified in the cultivar ‘Mego’ from Japan. CONCLUSIONS: These microsatellite markers can be used to investigate the genetic diversity, population structure, and gene flow of H. nobilis var. japonica.